Sedimentary records of chironomids and pigments from Wanghu Lake (middle Yangtze floodplain, China) - Zeng, Linghan; Engels, Stefan; Swann, George E A; Chen, Xu; Huang, Xianyu; Cao, Yanmin; McGowan, Suzanne (PANGAEA, 2024)
The sedimentary chironomids and pigments in two Yangtze floodplain (China) lake sediment cores since 1800s CE. The sediment cores were dated using lead-210 with the constant rate of supply (CRS) model. Chironomids were ananlyzed following standard procedures. About 10 g wet samples were firstly deflocculated using 10% potassium hydroxide (KOH) in a 75 °C water bath for about 15 minutes. Then, sediments were gently washed through 212 μm and 90 μm sieves with water after which the residues on the sieves were backwashed into a sorting tray. Chironomid head capsules were picked out individually using fine forceps under a dissecting microscope. The chironomid head capsules were identified using a microscope at ×100/×400 magnification. At least 50 head capsules were picked out from each sample to make the results and interpretations statistically robust.